2015
DOI: 10.1002/etc.3037
|View full text |Cite
|
Sign up to set email alerts
|

Salts affect the interaction of ZnO or CuO nanoparticles with wheat

Abstract: Exposure to nanoparticles (NPs) that release metals with potential phytotoxicity could pose problems in agriculture. The authors of the present study used growth in a model growth matrix, sand, to examine the influence of 5 mmol/kg of Na, K, or Ca (added as Cl salts) and root exudates on transformation and changes to the bioactivity of copper(II) oxide (CuO) and zinc oxide (ZnO) NPs on wheat. These salt levels are found in saline agricultural soils. After 14 d of seedling growth, particles with crystallinity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 75 publications
(130 reference statements)
2
17
0
Order By: Relevance
“…It should be noted that while lateral root induction is related to auxin regulation, this phenomenon is not unique to nanoparticles. Stewart et al (2015)have reported similar findings for ZnO NPs and metal ions.…”
Section: Mechanisms For Metallic Nanoparticle Effectssupporting
confidence: 64%
“…It should be noted that while lateral root induction is related to auxin regulation, this phenomenon is not unique to nanoparticles. Stewart et al (2015)have reported similar findings for ZnO NPs and metal ions.…”
Section: Mechanisms For Metallic Nanoparticle Effectssupporting
confidence: 64%
“…The CuONPs were modeled with a finite type IV solid phase of crystalline tenorite, calculated as total mass of CuONPs added initially to the Magenta boxes per volume of solution at the end of the growth period. X‐ray diffraction analysis of the CuONPs showed the patterns typical for a monoclinic structure of tenorite (Stewart et al ). Currently, the stability constant for nanoparticulate tenorite is not reported in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…In a study involving bean, a reduction of the shoot levels of Fe, Mn, and Zn was observed in the presence of CuO NPs, but cotreatment of the CuO NP-exposed plants with ZnO NPs lowered the shoot level of Cu from CuO NPs, likely due to the alleviation by ZnO NPs of the inhibition of Fe reductase activity induced by CuO NPs in the plant . Secondly, as shown in a study with wheat, the induction of lateral root proliferation occurs with certain micronutrients, whether as ions or NPs (Stewart et al 2015 and references therein). These findings indicate the role that ions released from NPs might be playing.…”
Section: Uptake Of Nanoparticulate Nutrientsmentioning
confidence: 89%